2004
DOI: 10.3171/ped.2004.100.2.0212
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hamartoma secreting corticotropin-releasing hormone

Abstract: The authors describe a unique case of a 2-year-old boy with a hypothalamic hamartoma secreting corticotropin-releasing hormone (CRH). The patient presented with a history of behavioral disturbances progressing over 12 months. His neurological status was intact. Magnetic resonance imaging demonstrated a 1.8 x 1.6 x 1.2-cm isointense, nonenhancing hypothalamic lesion. Endocrinological workup revealed elevated serum CRH and adrenocorticotropic hormone levels, nonsuppression with low-dose dexamethasone, and partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This effect could be emulated by the mathematical model in Table 1 as a consequence of an increased CRH output caused by LHK (Fig 3B). This novel finding strengthens the notion of an important role of CRH in the pathophysiology of mood disorders [92], and is in agreement with clinical data on hypothalamic hamartoma–patients with this non-neoplastic tumor present with mood symptoms [93] and also elevation in CRH concentration [94]. However, it might seem contradictory to other data of emerging manic symptoms in patients receiving corticosteroid treatment for medical conditions (reviewed in [95]).…”
Section: Discussionsupporting
confidence: 87%
“…This effect could be emulated by the mathematical model in Table 1 as a consequence of an increased CRH output caused by LHK (Fig 3B). This novel finding strengthens the notion of an important role of CRH in the pathophysiology of mood disorders [92], and is in agreement with clinical data on hypothalamic hamartoma–patients with this non-neoplastic tumor present with mood symptoms [93] and also elevation in CRH concentration [94]. However, it might seem contradictory to other data of emerging manic symptoms in patients receiving corticosteroid treatment for medical conditions (reviewed in [95]).…”
Section: Discussionsupporting
confidence: 87%
“…Voyadzis et al . report a single case with excessive corticotropin‐releasing hormone (CRH) secretion in a 2‐year‐old boy with HH characterized clinically by excessive behavioral lability and paroxysms of rage.…”
Section: Other Endocrine Manifestations Of Hhmentioning
confidence: 88%
“…Voyadzis et al 80 report a single case with excessive corticotropin-releasing hormone (CRH) secretion in a 2-yearold boy with HH characterized clinically by excessive behavioral lability and paroxysms of rage. There were no physical signs of endocrinopathy, but CRH and adrenocorticotropic hormone (ACTH) levels were elevated and did not suppress with dexamethasone administration.…”
Section: Other Endocrine Manifestations Of Hhmentioning
confidence: 95%
“…To date, only Voyadzis Hypothalamic hamartoma simulating a suprasellar arachnoid cyst: resolution of precocious puberty following microsurgical lesion resection et al have demonstrated corticotropin-releasing hormone (CRH) immunostaining in an HH. 56 We report the first case of a symptomatic HH with a solid CRH-positive component and associated tumor cyst in an 18 month-old girl presenting with central precocious puberty. We discuss the pathological features of this hamartoma along with approaches to its resection and management.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Our case has shown CRH immunoreactivity in the solid part of the lesion; however, there are conflicting opinions on the role of CRH in the causation of precocious puberty in these patients. 16,22,56 …”
Section: Treatment Of Hhmentioning
confidence: 99%